2004
DOI: 10.1080/1478336042000255497
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Channels that Facilitate a Total Quality Culture

Abstract: It is generally agreed that the culture of an organisation is a function of its values, beliefs and behavioural practices and that the influence of culture on an organisation is powerful and pervasive. There is also broad agreement that total quality management (TQM ) is a management paradigm that propagates certain values, behaviour and working methods. Moreover, that the successful introduction and practice of a total quality management approach requires close attention to, and more often than not modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 95 publications
0
47
0
2
Order By: Relevance
“…Teamwork is a work arrangement that arguably has the capacity to enable cooperation and effective individual involvement and it represents a way of working (Gallear and Ghobadian, 2004). Teamwork includes identifying the needs of all groups and organizations involved in decision making, trying to find solutions that will benefit everyone involved, and sharing responsibility and credit (Ciampa, 1991).…”
Section: Tqm Practicesmentioning
confidence: 99%
“…Teamwork is a work arrangement that arguably has the capacity to enable cooperation and effective individual involvement and it represents a way of working (Gallear and Ghobadian, 2004). Teamwork includes identifying the needs of all groups and organizations involved in decision making, trying to find solutions that will benefit everyone involved, and sharing responsibility and credit (Ciampa, 1991).…”
Section: Tqm Practicesmentioning
confidence: 99%
“…We also encourage research that builds on our results and test the external validity of our propositions. Following Gallear and Ghobadian (2004), we argue that the potential contribution of Lean may be lost if its theoretical and rhetorical foundation is not critically assessed and defined.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have pointed to the gap that often exists between the rhetoric and reality of change initiatives (Zbaracki, 1998, Gallear and Ghobadian, 2004, Bendell, 2005, Venkateswarlu and Nilakant, 2005, Soltani et al, 2007, Green, 2012. Several studies have shown that there are considerable differences between Lean as practiced in reality compared to many descriptions in literature (Poksinska et al, 2010, Brännmark et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Mamafih aynı zamanda TKY, yorumlanan değerleri doğrultusunda bir işletmenin değerlerini değiştiren bir araçtır. Bir başka açıdan bakıldığında, TKY, faaliyetlerle desteklenen bir değerler setini içerir (Gallear ve Ghobadian, 2004:1045-1047. (Şekil 5) Deming'e göre, TKY, bir işletmede geleneksel yönetimden sürekli iyileştirme yönetim stiline doğru radikal bir kültürel değişime ihtiyaç duyan bir yönetim felsefesidir.…”
Section: Toplam Kali̇te Yöneti̇m Uygulamalarinda öRgüt Kültürü Ve İkli̇munclassified